Intrapericardial administration of mesenchymal stem cells in a large animal model: a bio-distribution analysis. - Rebeca Blázquez; Francisco Miguel Sánchez-Margallo; Verónica Crisóstomo; Claudia Báez; Juan Maestre; Mónica García-Lindo; Alejandra Usón; Verónica Álvarez; Javier G Casado (PLoS ONE, 2015)
The appropriate administration route for cardiovascular cell therapy is essential to ensure the viability, proliferative potential, homing capacity and implantation of transferred cells. At the present, the intrapericardial administration of pharmacological agents is considered an efficient method for the treatment of cardiovascular diseases. However, only a few reports have addressed the question whether the intrapericardial delivery of Mesenchymal Stem Cells (MSCs) could be an optimal administration route. This work firstly aimed to analyze the pericardial fluid as a cell-delivery vehicle. Moreover, the in vivo biodistribution pattern of intrapericardially administered MSCs was evaluated in a clinically relevant large animal model. Our in vitro results firstly showed that, MSCs viability, proliferative behavior and phenotypic profile were unaffected by exposure to pericardial fluid. Secondly, in vivo cell tracking by magnetic resonance imaging, histological examination and Y-chromosome amplification clearly demonstrated the presence of MSCs in pericardium, ventricles (left and right) and atrium (left and right) when MSCs were administered into the pericardial space. In conclusion, here we demonstrate that pericardial fluid is a suitable vehicle for MSCs and intrapericardial route provides an optimal retention and implantation of MSCs.